The comparison of largemouth bass (Micropterus salmoides) fed trash fish and formula feeds: Growth, flesh quality and metabolomics - Xu, Xiaoying; Yang, Hang; Xu, Zhen; Li, Xiaoqin; Leng, Xiangjun (Frontiers in Nutrition, 2022)
This study compared the growth, flesh quality and metabolomics of largemouth bass (Micropterus salmoides) fed trash fish and formula feeds. Trash fish (TF), self-made feed (SF) and commercial feed (CF) were prepared with crude protein levels of 172.2 g/kg, 503.5 g/kg and 504.1 g/kg (666.2 g/kg, 547.3 g/kg and 535.1 g/kg based on dry matter). Then, the three diets were fed to largemouth bass with an initial body weight of 75.0 g for 12 weeks. SF and CF groups presented significantly lower feed intake (FI), feed conversion ratio (FCR) and higher protein efficiency ratio (PER) than TF group based on dry matter basis without affecting the weight gain (P < 0.05). The yellowness (b*) in dorsal muscle, flesh heat-insoluble collagen and free delicious amino acids contents in SF group were significantly higher (P < 0.05), while drip loss were significantly lower (P < 0.05) than those of TF group. Compared to TF group, SF and CF groups showed significantly higher flesh polyunsaturated fatty acids (PUFAs), n-3 PUFAs and n-6 PUFAs contents, flesh hardness, shear force and muscle fiber density (P < 0.05), and lower flesh total free amino acids, essential amino acids, muscle fiber diameter, intestine villus height and muscular thickness (P < 0.05). The serum total protein, triglyceride and cholesterol levels in SF group were significantly lower than those in TF and CF groups (P < 0.05). In muscle metabolomics, 177 differential metabolites were detected between SF and TF groups, which mainly enriched in pathways as biosynthesis of amino acid, histidine metabolism, glycine, serine and threonine metabolism, etc. Conclusively, feeding largemouth bass with formula feeds improved flesh fatty acid profile and flesh texture without negative effects on growth, but the flesh free amino acids contents were lower than the fish fed trash fish.